Reactive Flash Sintering of Ceramics: A Review. Issue 5 (14th September 2022) - Yoon, Bola; Avila, Viviana; Lavagnini, Isabela R.; Campos, João V.; Jesus, Lílian M.
Abstract : As a novel electric field‐assisted sintering technique, flash sintering (FS) has gained significant interest over the past decade due to its compelling time and cost efficiency. This technique is originally used to densify ceramic samples in a few seconds by applying an electric field while heating a material. Recently, FS has been extended to enable simultaneous synthesis and sintering of ceramics in a derived method called reactive flash sintering (RFS). This review provides a comprehensive overview of RFS for a better understanding of the process and to draw the attention of scientists and engineers to this new technique. Abstract : This article provides a comprehensive overview of reactive flash sintering (RFS), a cost‐effective method that allows for the simultaneous synthesis and sintering of ceramics; for a better understanding of the process and to draw the attention of scientists and engineers to this novel technique.